Phosphinocyclodextrins as confining units for catalytic metal centres. Applications to carbon–carbon bond forming reactions - Jouffroy, Matthieu; Gramage-Doria, Rafael; Sémeril, David; Armspach, Dominique; Matt, Dominique; Oberhauser, Werner; Toupet, Loïc (Beilstein Journal of Organic Chemistry, 2014)
The capacity of two cavity-shaped ligands, HUGPHOS-1 and HUGPHOS-2, to generate exclusively singly phosphorus-ligated complexes, in which the cyclodextrin cavity tightly wraps around the metal centre, was explored with a number of late transition metal cations. Both cyclodextrin-derived ligands were assessed in palladium-catalysed Mizoroki–Heck coupling reactions between aryl bromides and styrene on one hand, and the rhodium-catalysed asymmetric hydroformylation of styrene on the other hand. The inability of both chiral ligands to form standard bis(phosphine) complexes under catalytic conditions was established by high-pressure NMR studies and shown to have a deep impact on the two carbon–carbon bond forming reactions both in terms of activity and selectivity. For example, when used as ligands in the rhodium-catalysed hydroformylation of styrene, they lead to both high isoselectivity and high enantioselectivity. In the study dealing with the Mizoroki–Heck reactions, comparative tests were carried out with WIDEPHOS, a diphosphine analogue of HUGPHOS-2.
Keywords: asymmetric hydroformylation; cyclodextrin; Heck reaction; homogeneous catalysis; palladium; phosphine; rhodium